'Capital as power': an alternative reading of India's post-2011 economic slowdown. Issue 1 (2nd January 2023) - Kothakapa, Gouthami; Sirohi, Rahul A.
ABSTRACT: A study of the post-2011 economic slowdown in India that challenges liberal and Keynesian interpretations by drawing on Nitzan and Bichler's argument of 2009 that modern-day capitalist activity is shaped primarily by differential rather than absolute accumulation and the accumulation of power so as to squeeze and lock out competitors, monopolize resources, sabotage production and acquire unused capacity. In an exploration of the deep-rooted entanglements of power, crisis and accumulation, firm-level data from India are examined to show that a growth slowdown, economic crisis and destruction of the livelihoods of millions of people have provided an opportunity for top corporate houses to entrench their power and wealth. Crisis, in other words, has been good for business.